Effectiveness of paracervical block for pain relief in women undergoing hysterosalpingography in Bayelsa State, South-South Nigeria: a randomized control trial - Kiridi, Enefia Kelvin; Oriji, Peter Chibuzor; Ugwoegbu, Johnpatrick Uchenna; Abasi, Isaac Joel (International Journal of Clinical Trials, 2022)
Background: One of the major short comings of hysterosalpingography is discomfort and/or pain for the patient during or after the investigative modality; and this is a major cause of anxiety for many patients. Objectives were to compare the effectiveness of paracervical block with 2% lignocaine and placebo in pain reduction when undergoing hysterosalpingography. Methods: This randomised control trial was conducted at the radiology departments and infertility clinics of the Federal Medical Centre, Yenagoa and Niger Delta University Teaching Hospital, Okolobiri, both in Bayelsa State, Nigeria, from July 2021-February 2022. Three hundred and eighty infertile women undergoing hysterosalpingography were assigned into two groups. Women in group I received paracervical block, while the women in group II received placebo. Data were analysed using statistical product and service solutions for windows® version 25. Results were presented in frequencies and percentages for categorical variables; mean and standard deviation for continuous variables. Student’s t-test was used to compare sample means; and Chi-square for associations. Results: The mean pain score ± SD for group I was 3.8±2.6, while that in group II was 6.2±2.2. The difference between the means was statistically significant (t=9.77; p=0.001). While 140 (73.7%) women experienced moderate pain in group II, 70 (36.8%) women in Group I experienced moderate pain. Conclusions: Our study revealed that paracervical block improved the overall pain score of women undergoing hysterosalpingography, although a significant proportion of the women expressed some pain during instillation of contrast media.